A comparison of the numerical predictions of the supersonic combustion of Hydrogen using the S-A and SST k – ω models. (11th August 2009) - Kumaran, K.; Babu, V.
In the present work, the influence of the turbulence model on the numerical predictions of supersonic combustion of hydrogen in a model combustor is investigated. Three dimensional, compressible, turbulent, reacting flow calculations using the Shear Stress Transport (SST) k – ω model have been carried out. The results are compared with earlier results obtained using the Spalart-Allmaras model. The effect of detailed chemistry on the predictions of heat release and combustion efficiency is also investigated for one injection scheme. The calculations show that the mixing and hence the heat release is over predicted by the SA model. Whereas, the peak values for pressure and temperature are predicted better by the SST k – ω model. This investigation demonstrates the importance of the use of a two equation turbulence model over a one equation model for studying such complex flow phenomena.